Barbados. Significant achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in Barbados during 2020 are identified, with respect to the needs and interests of the country, identifying problems in trade, sustainable development, agro-tourism, food security and gender equity. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized. Finally, for the recovery of the rural sector due to the post-COVID-19, support was provided to develop related campaigns to highlight the important role of farmers during the pandemic.